Problems and Solving Ways of the Standards of Contemporary Georgian Literary Language - Saghinadze, Rusudan (Actual Problems of Kartvelology, 2013)
Standards of contemporary Georgian literary language have already been fixed. But something has changed in Georgian Language. Many phenomena have appeared in the process of form researching and strengthening. The opposition is very clear between colloquial and literary language. In addition to this, there are some problems even in Georgian literary language. In particular: a) sometimes the same principle is not applied while setting standards. For example, on the one hand, the following forms are considered to be false without ‘s’: ‘chemken’, ‘chem tsinashe’, ‘chem tsin’, ‘chem mier’… On the other hand, the forms with ‘s’ is believed to be true: ‘chems iqet’, ‘chems shemdeg’… b)Sometimes the norms implies the parallelism: ‘vkitkhe||vhkitkhe’, ‘vdzulvar||vsdzulvar’, ‘movtkhove||movstkhove’, ‘movtatse||movstatse’… There are verbs without ‘s’ in written and colloquial speech: ‘vkitkhe’, ‘vdgavar’, ‘movtkhove’.; In general the principle of forms semantic difference is very strong, that is not very highlighted in the principles of making standards. There are many ways to solve the problems but it should be better to create the state committee that establishes the new standards of Georgian literary language.